ANALYSIS OF THE ELEMENT OF USURY IN SHARIA ONLINE FINANCING: A case study in Alami Syariah and Investree Online Financing Company of Indonesia - Sarah, Siti; Abubakar, Ali; Ahmed, Fraz (JURISTA: Jurnal Hukum dan Keadilan, 2023)
Sharia online financing is guaranteed by the Financial Services Authority by referring to the DSN MUI Fatwa on Financing Services Based on Financial Information Technology Based on Sharia Principles, which avoids usury, gharar, maysir and tadlis. The purpose of this research is to find out how the mechanism of sharia online financing services and to find out how the analysis of the elements of usury in sharia online financing on its suitability with the DSN-MUI Fatwa on Financing Services. This research method is empirical juridical, where primary data is obtained from interviews. While secondary data is obtained from reference sources related to this research. The results showed that the additional element at the time of returning the financing on the Alami and Investree applications was not categorised as usury (interest). In the transaction, this addition is an ujrah / fee that will be received by the parties for their services, as implemented by Alami Sharia and Investree Syariah online financing where there are funding providers and funding recipients who authorise these online financing platforms to transfer receivables settlement. On the basis of marketplace services that have brought the two parties together, the Alami and Investree platforms are entitled to an ujrah of 1% - 5% for fees for their services, the lender/funder is also entitled to a profit / ujrah from the funds provided to be managed by the borrower, the margin / ujrah that can be obtained is 12% - 20% effective p.a. according to the level of risk and the term chosen at the time of financing